TGase-induced intracellular aggregation of Fe3O4 nanoparticles for increased retention and enhanced T2 MRI. (14th May 2019) - Gao, Xuefeng; Liu, Yang; Li, Yingying; Niu, Xiaoyan; Cao, Jing; Li, Xiaomin; Zhang, Yapei; Tan, Dongzhi; Wang, Wei; Yuan, Zhi
Abstract : TGase-induced aggregation strategy was used to increase the NPs-Q&K retention in the tumor and enhance the T 2 MRI. Abstract : Superparamagnetic iron oxides (SPIO) are attractive MRI contrast agents but suffer from limited sensitivity and low tumor specificity. In this study, two sets of SPIO nanoparticles (SPIONPs) were synthesized that were designed to selectively crosslink upon sensing transglutaminase (TGase), which is highly expressed at tumor site, thereby leading to the formation of SPIO nanocluster with T 2 signal enhancement properties. For this purpose, SPIONPs with glutamine and lysine surfaces were synthesized. In vitro studies showed that the SPIONPs could crosslink to form aggregates with diameter of 1.3 μm in the presence of TGase and showed a 1.8 fold enhancement in r 2 relaxivity compared with the dispersed state. The cellular uptake results illustrated that the SPIONPs could crosslink in high TGase expressing HeLa cells and showed an aggregation-induced retention effect compared with the controlled MCF-7 cell-line (about 1.9 fold). Simultaneously, the administration of the SPIONPs in the HeLa tumor-bearing mice verified the TGase-responsive aggregation and tumor enrichment of the nano contrast agent. MRI imaging also demonstrated the T 2 signal enhancing ability of the TGase-responsive SPIONPs; the Δ T 2 signal of the SPIONPs in the HeLa tumor-bearing group was about 2.3 fold higher than the MCF-7 group and the TGase-inhibitor treated group.